Creation of a Laboratory Fog Chamber for Testing Optical Sensors (European Journal of Engineering Science and Technology, 2024)
LIDAR sensors and systems are gaining popularity, but their effectiveness can be compromised by light reflections in foggy conditions. To address the need for small, laboratory-scale testing systems, a fog chamber was developed and tested to have a laboratory environment. Two different methods to produce fog were evaluated: hot steam and ultrasonic nebulizers. The cold fog from ultrasonic nebulizers was more prone to stratification, while the hot fog from hot steam produced rather disturbing condensation for the measurement. All this was solved by implementing improving aids such as a ventilation and windscreen wiper system. First to mitigate the fog stratification with help of circulation and second to prevent condensation with help of wiping the windows in the measurement path. Ultimately, the ultrasonic nebulizers showed their strengths in the experiment due to the lower influence of the enhancement aids on the signal quality, which is why they are recommended as a fog source.